A Study on the Use of Kim Kwang-seok’s “Love That Hurts Too Much Was Not Love” as Korean Language Educational Material: A Teaching Method for Paradoxical Realization and Expressions of Emotional Intensification - Kim Hyong Jong (Global Scientific Publishing, 2026)
This study proposes a method for teaching Korean learners about Korean emotional sensibilities regarding separation and philosophical reflections on love by utilizing the song “Love That Hurts Too Much Was Not Love” by the singer Kim Kwang-seok as Korean language educational material for foreign learners. This song is an advancedlevel text that conveys paradoxical realization through the opposing concepts of “pain” and “love,” and it is rich in metaphorical expressions that symbolize abstract suffering throughout its lyrics. By integrating psychological theories of emotional education with linguistic grammatical analysis, this study identifies the educational value of realization-marking sentence endings and expressions of emotional intensification found in the song lyrics. Based on this analysis, a three-stage teaching–learning model is designed to enhance learners’ logical thinking skills and their ability to express complex emotions, along with specific discussion and writing activities.
Keywords: paradoxical realization; emotional intensification expressions